Response of one way asymmetric plans to bi-directional earthquakes - Hernández, Julio; López, Oscar (Rev. Téc. Fac. Ing. Univ. Zulia)
This paper aims to investigate the relative importance of the parameters that influence the elastic torsional response of one-way asymmetric buildings: eccentricity, torsional flexibility, damping and spectral shape, considering the simultaneous application of two orthogonal components of serviceability seismic motions. The overall global response is considered but the emphasis is directed to the response of the resisting elements of the plan. It is shown that bi-directional seismic motion should be include in the dynamic analysis in order to reach an accurate determination of responses of the resisting elements located along the symmetric direction of the plan. It is concluded that seismic codes must incorporate greater amplifications for the design of the stiff side of the plan and include the simultaneous action of the two horizontal seismic components.